2005
DOI: 10.1159/000090084
|View full text |Cite
|
Sign up to set email alerts
|

A Centenary of Auscultatory Blood Pressure Measurement: A Tribute to Nikolai Korotkoff

Abstract: In 1905, Dr. Nikolai Korotkoff (1874–1920), a Russian surgeon, discovered a simple and precise technique to measure arterial pressure. He was born on 26th February 1874 in the central Russian city of Kursk. Korotkoff graduated from the Medical Faculty of Moscow University in 1898, but he worked later in the Surgical Clinic at the Imperial Military Medical Academy in St. Petersburg (Russia). Korotkoff served as a military surgeon during the Russo-Japanese War (1904–1905) and his major efforts were to find relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Systole and diastole were determined based on Kortokoff sounds (Paskalev et al 2005). Brachial BP was taken in duplicate and the average of the two values was recorded and used for subsequent analysis.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Systole and diastole were determined based on Kortokoff sounds (Paskalev et al 2005). Brachial BP was taken in duplicate and the average of the two values was recorded and used for subsequent analysis.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Although Korotkoff already observed that with his auscultatory technique SBP was approximately 10-12 mmHg higher compared with palpatory SBP measurements [4,5], a formal comparison on the difference between auscultatory and palpatory SBP was never reported. A previous Riva-Rocci revisited van der Hoeven et al 53 The upper row shows the percentage all readings (n ¼ 320) of which the difference between the pSBP and the aSBP is 5 mmHg, 10 mmHg, 15 mmHg, or >15 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to blood pressure (BP) devices earlier used in the nineteenth century, his sphygmomanometer with inflatable cuff provided an easy way to perform sufficiently reliable, noninvasive, SBP measurements [1][2][3]. Nine years later, in 1905, the Russian surgeon Nikolai Korotkoff observed specific sounds when compressing arterial vessels, which eventually led to the auscultatory method for BP measurement [4,5]. Although auscultatory BP measurement is the present standard for clinical BP measurement, palpatory BP measurement is still embedded in current medical practice, as it is used to estimate the SBP level before commencing auscultatory BP measurement [6].…”
Section: Introductionmentioning
confidence: 99%
“…In 1828, Pouseiulle invented a device he called a 'hemodynamometer' that was able to measure blood pressure using a column of mercury. The hemodynamometer, however, required the insertion of a long U-shaped pipe inside an artery, and thus was deemed clinically inappropriate [7]. Carl Ludwig and Jules Herrison separately developed devices that were able to record blood pressure waves uninvasively.…”
mentioning
confidence: 99%
“…He stated that the normal systolic blood pressure was between 135 and 165 mmHg, and observed that in individuals with Bright's disease (also known as glomerulonephritis) [2] it could be as high as 200 mmHg [7]. Von Basch identified a pathological entity characterized by elevated blood pressure he called 'latent atherosclerosis', and which probably represents today's essential hypertension [9].…”
mentioning
confidence: 99%